Wastewater treatment in a small domestic-productive unit, using alternative technologies - Pérez Rodríguez, Cynthia; Coto Campos, Juana María; Salgado Silva, Viviana; Herrera Núñez, Jacqueline; Fernández Araya, José Francisco; Benavides Benavides, Cristina (Uniciencia, 2013)
A small producer has built in his property a low cost non- conventional wastewater treatment, characterized by maintenance and operation easiness, and aesthetical suitability; complemented with the implementation of environmentally friendly practices. The system involves reduction in water consumption, utilization of biodegradable products, treatment of wastewater and reuse, use of alternative energies, gravity watering, among others. Sewage and grey waters of the house are collected separately; the first one goes to a biodigester, followed by two small ponds with floating vegetation. Grey waters are treated in a series of three small ponds, with aquatic plants. The effluents of both subsystems are getting together and conducted to other two ponds; the final effluent is discharged into the Catalina River, where it was determined the Water Quality Index of the NSF and the BMWP Index, modified to Costa Rica. The system was evaluated for nine months; it was very successful in reduction of BOD, phosphates and nitrates, however, it is not as effective in the removal of fecal coliformes. In general terms, the effluent does not affect the water quality of the Catalina River.